REPRESENTATION OF CUSTOMER LOYALTY IN AQUA’s ADVERTISEMENT “SAMBUT KEBAIKAN RAMADHAN BERSAMA AQUA” - Karim, Iklilul; Utari, Prahastiwi; Hastjarjo, Sri (ANDHARUPA: Jurnal Desain Komunikasi Visual & Multimedia, 2024)
Abstract. Relize or not, advertising is very close to human life. Mass media can display tens or even hundreds of advertisements every day. Therefore, effective and attractive advertisements are needed to attract customers. In general, advertising uses the hard selling method, but now it has turned into soft selling, which does not introduce or sell products directly. Therefore, this research will discuss the representation of customer loyalty in AQUA's advertisement "Sambut Kebaikan Ramadan Bersama AQUA". The method used is qualitative with Roland Barthes semiotic analysis. The results of this study show that AQUA's advertisement "Sambut Kebaikan Ramadan Bersama AQUA'' successfully portrays customer loyalty through the usage of strong signs and hidden meanings. At the denotative level, this AQUA advertisement presents an image of loyal AQUA customers who consume AQUA products joyfully during Ramadan. At the connotative level, this advertisement connects the usage of AQUA products with the values of kindness, spirituality, and brotherhood associated with Ramadan. At the mythological level, this AQUA advertisement builds a narrative that describes AQUA’s customers as part of a solid and loving community. In this context, customer loyalty is represented as a form of adherence to the values embraced by the community, which is signified by the consumption of AQUA’s products.Keywords: Advertisement, Representation, Loyalty, Semiotic